ESTIMATION OF BIOCHEMICAL INDEX IN EYE INFLAMMATION DISEASES - Djamalova, Sh.A.; Babadjanova, Sh.A.; Kurbanova, Z.Ch.; Musaeva, N.B.; Sulaymonov, O.O. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the dynamics of biochemical parameters of lipid peroxidation (LPO) and antioxidant protection (AOD) in the lacrimal fluid in patients with conjunctivitis, blepharitis and keratitis. Materials and methods: Studies of the level of malondialdehyde and the activity of superoxide dismutase and catalase in the lacrimal fluid were carried out in patients with conjunctivitis, blepharitis and infectious keratitis. Results: Inflammatory diseases of the eyes are manifested by the intensification of lipid peroxidation and changes in the activity of the enzymes of the antioxidant system of the tear fluid. Conclusions: The severity of lipid peroxidation and changes in the activity of AOS enzymes tear fluid depends on the severity of the pathology.